Community demands in restoring the function of the Row in accordance with the Site Plan of Sungai Langkai Village, Rt002/Rw007 Batam City - Ruth Celline Deon Br Galingging; Nanik Rahmawati; Marisa Elsera (Social Issues Quarterly, 2023)
Land conflicts are often encountered in both urban and rural areas, accompanied by their diversity. For example, conflicts between the community and developers from a private company with the initials PT NSA, as well as local governments who participate in supporting the road function conversion that occurred in Sungai Langkai Sub-district, RT002/RW007, Batam City. The land problem resulted in changes in road access function that did not comply with the site plan in that area. This conversion led the community to take various rejection actions to maintain the function of the roadside in accordance with the established land rules for the comfort of their living environment. This study aims to determine the demands made by the community to maintain the function of the roadside. The data collection techniques used in this study were structured interviews, participant observation, and documentation. The sampling technique used was purposive sampling. This study uses Lewis Alfred Coser's theory which views conflicts not only as negative but also positive. The findings of this study describe negative impacts. In addition, conflicts also have positive impacts on community groups in carrying out their demands, such as building stronger solidarity by holding meetings to determine the strategies to be taken and the spirit of the residents to help each other, whether in the form of money, time, or transportation.